2015
DOI: 10.1890/es14-00436.1
|View full text |Cite
|
Sign up to set email alerts
|

When hot rocks get hotter: behavior and acclimatization mitigate exposure to extreme temperatures in a spider

Abstract: Abstract. In environments where animals have a high probability of encountering temperatures close to their thermal limits, animals with the capacity to minimize the chances of encountering these temperatures will be advantaged. We investigated the physiological and behavioral mechanisms used by flat rock spiders, Morebilus plagusius, to avoid encountering lethal or sub-lethal temperatures on sandstone outcrops by measuring their critical thermal maximum (CT Max ) in spring and summer and quantifying their ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…This may manifest in spatially explicit actions such as an organism moving between discrete shade locations (Lagarde et al , Goller et al , Sears et al ), using cover to mitigate convective heat loss (Sherfy and Pekins ), or nest site selection (Carroll et al , Hovick et al ). Accordingly, scale dependency of thermal selection in response to shade has been shown for organisms ranging from spiders (Araneae); van den Berg et al ) to moose ( Alces alces ; Demarchi and Bunnell , van Beest et al ). In this regard, shade (or lack thereof) can be viewed as a critical resource, yet is often not viewed in that way by land managers, especially relative to the scale and distribution that it may be accessible to organisms.…”
Section: How Temperature Affects Space Use and Behaviormentioning
confidence: 99%
“…This may manifest in spatially explicit actions such as an organism moving between discrete shade locations (Lagarde et al , Goller et al , Sears et al ), using cover to mitigate convective heat loss (Sherfy and Pekins ), or nest site selection (Carroll et al , Hovick et al ). Accordingly, scale dependency of thermal selection in response to shade has been shown for organisms ranging from spiders (Araneae); van den Berg et al ) to moose ( Alces alces ; Demarchi and Bunnell , van Beest et al ). In this regard, shade (or lack thereof) can be viewed as a critical resource, yet is often not viewed in that way by land managers, especially relative to the scale and distribution that it may be accessible to organisms.…”
Section: How Temperature Affects Space Use and Behaviormentioning
confidence: 99%
“…The reason is that in summer the temperature inside the rock is lower than the air temperature: the animal’s body, closely adjacent to the rock, cools faster due to the higher (than air) thermal conductivity of the rock. It was shown that spiders [ 44 , 45 ] and snakes [ 46 ] choose stones of a suitable size for shelters to maintain optimal body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Although these effects have been explored for diverse organisms (e.g. (Berg et al, 2015;Huey et al, 1989) ), we still lack a quantitative assessment of the relationship between body size and the thermal coupling with the surfaces on which organisms live.…”
Section: Introductionmentioning
confidence: 99%